Alter egos : Hillary Clinton, Barack Obama, and the twilight struggle over American power - Landler, Mark (New York : Random House, 2016)
"The deeply reported story of two supremely ambitious figures, Barack Obama and Hillary Clinton--archrivals who became partners for a time, trailblazers who share a common sense of their historic destiny but hold very different beliefs about how to project American power. In Alter Egos, veteran New York Times White House correspondent Mark Landler takes us inside the fraught and fascinating relationship between Barack Obama and Hillary Clinton--a relationship that has framed the nation's great debates over war and peace for the past eight years. In the annals of American statecraft, theirs was a most unlikely alliance. Clinton, daughter of an anticommunist father, was raised in the Republican suburbs of Chicago in the aftermath of World War II, nourishing an unshakable belief in the United States as a force for good in distant lands. Obama, an itinerant child of the 1970s, was raised by a single mother in Indonesia and Hawaii, suspended between worlds and a witness to the less savory side of Uncle Sam's influence abroad. Clinton and Obama would later come to embody competing visions of America's role in the world: his, restrained, inward-looking, painfully aware of limits; hers, hard-edged, pragmatic, unabashedly old-fashioned. Spanning the arc of Obama's two terms, Alter Egosgoes beyond the speeches and press conferences to the Oval Office huddles and South Lawn strolls, where Obama and Clinton pressed their views. It follows their evolution from bitter rivals to wary partners, and then to something resembling rivals again, as Clinton defined herself anew and distanced herself from her old boss. In the process, it counters the narrative that, during her years as secretary of state, there was no daylight between them, that the wounds of the 2008 campaign had been entirely healed. The president and his chief diplomat parted company over some of the biggest issues of the day: how quickly to wind down the wars in Iraq and Afghanistan; whether to arm the rebels in Syria; how to respond to the upheaval in Egypt; and whether to trust the Russians. In Landler's gripping account, we venture inside the Situation Room during the raid on Osama bin Laden's compound, watch Obama and Clinton work in tandem to salvage a conference on climate change in Copenhagen, and uncover the secret history of their nuclear diplomacy with Iran--a story with a host of fresh disclosures. With the grand sweep of history and the pointillist detail of an account based on insider access--the book draws on exclusive interviews with more than one hundred senior administration officials, foreign diplomats, and friends of Obama and Clinton--Mark Landler offers the definitive account of a complex, profoundly important relationship. As Barack Obama prepares to relinquish the presidency, and Hillary Clinton makes perhaps her last bid for it, how both regard American power is a central question of our time. Advance praise for Alter Egos "A superb journalist has brought us a vivid, page-turning, and revelatory account of the relationship between Barack Obama and Hillary Clinton, as well as of their statecraft. Alter Egoswill make a signal contribution to the national debate over who should be the next American president."--Michael Beschloss, bestselling author of Presidential Courage "Mark Landler, one of the best reporters working in Washington today, delivers an inside account of Hillary Clinton's relationship with Barack Obama that brims with insight and high-level intrigue. It's both fun to read and eye-opening."--Jane Mayer, bestselling author of Dark Money: The Hidden History of the Billionaires Behind the Rise of the Radical Right"--
"New York Times White House correspondent Mark Landler goes behind the speeches and press conferences, to the Situation Room debates and picnic-table lunches, where Obama and Clinton honed their two competing worldviews: his, cautious, inward-looking, suffused with a sense of limits; hers, muscular, optimistic, unabashedly old-fashioned. Alter Egos is about two ambitious political archrivals from very different backgrounds who became partners for a time, trailblazers who share a common sense of their historical destiny but who hold fundamentally different beliefs about how to project American power. With all the sweep of a grand history--and enlivened by an insider's access and plenty of news--Landler digs deep into the complex relationship between these two leaders and gives us a different way to think about Obama's legacy and Clinton's promise"--
Includes bibliographical references (pages 355-357) and index.
Keywords: Obama, Barack; Clinton, Hillary Rodham; United States -- Foreign relations -- 2009-